Auswirkungen der digitalen Flexibilisierung des Fertigungsortes auf die Verteilung der Besteuerungsrechte – Ergebnisse von Modellrechnungen zum 3D-Druck-Verfahren - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren (Steuer und Wirtschaft)

Steuerliche Entlastungsmöglichkeiten für kleine und mittlere Unternehmen wegen der COVID-19-Pandemie - Giese, Henning; Graßl, Benjamin; Holtmann, Svea; Krug, Philipp (Deutsches Steuerrecht)

Tax Administrative Burden, Tax Relief and Investment during the Corona Crisis - Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Population Dynamics of Tax Avoidance with Crowding Effects - Lorenz, Johannes (Journal of Evolutionary Economics)
There are two ways for taxpayers to avoid paying taxes: legal tax optimization and illegal tax evasion. The government reacts by altering the law, and by conducting audits, respectively. These phenomena are modeled as a strategic interaction between all taxpayers: the more taxpayers optimize, the lower the optimization result as a consequence of the government tightening the tax law. The more taxpayers evade, the higher the risk of detection because of the tax agencies increasing the audit probability. It emerges that, in equilibrium, the population shares of optimizers and evaders are not interdependent; rather, they both increase to the detriment of the share of non-optimizing taxpayers. If the government reacts to changed optimization behavior with too large a delay, an equilibrium tax law cannot be reached. Tax codes should be updated rapidly in order to avoid a permanent change of the tax law, which is costly both for the legislator and the taxpayers facing legal uncertainty.

Was lange währt, wird endlich gut? Vorschau zur erwarteten Rechtsprechung des BFH zur grunderwerbsteuerlichen Konzernklausel - Kittl, Maximilian; Lorenz, Johannes (Deutsches Steuerrecht)

Tax Complexity for Multinational Corporations in South Africa - Evidence from a Global Survey - Hoppe, Thomas; Safaei, Reyhaneh; Singleton, Amanda; Sureth-Sloane, Caren (Tax Simplification - An African Perspective)
This chapter examines the drivers of corporate income tax complexity for multinational corporations in South Africa. Based on unique data from a global survey of tax consultants which was conducted in 2016 by Hoppe et al, novel insights can be provided into the complexity of the South African tax system. The data enable a comparison of South Africa with the global mean of tax complexity, as well as with its major trade and investment partners. It is further possible to distinguish between different areas of tax complexity, ie, tax code complexity (complexity inherent in the different regulations of the tax code) and tax framework complexity (complexity that arises from the features and processes of a tax system). Frequent changes in tax regulations, ambiguity and interpretation, as well as record-keeping, are found to be the most important complexity drivers in the tax code of South Africa. The analysis further highlights that anti-avoidance provisions, such as transfer pricing and controlled foreign corporation rules, are perceived as most complex. With respect to tax framework complexity, the poor disclosure of audit selection criteria, the lack of experience or technical skills of tax officers in the audit process and problems associated with tax refunds appear to be serious concerns. Even though South Africa’s overall tax system complexity does not seem to differ very much from other related countries, a closer look into the details reveals a number of future challenges.

Inheritance Tax Planning with Uncertain Future Payroll Expenses: An Analytical Solution to the Optimal Choice between Full and Standard Exemption - Diller, Markus; Späth, Thomas; Lorenz, Johannes (Journal of Business Economics)
Under the German Inheritance Tax and Gift Tax Act, the transfer of business assets can be exempted from taxation up to 100%. However, this exemption depends on the evolution of the company’s payroll, which is highly uncertain. We model the uncertain nature of payroll evolution using a Geometric Brownian motion. We obtain closed-form solutions for the expected effective exemption and for the expected effective tax rate. We find that the uncertainty effect is most pronounced for moderate negative and positive growth rates. Furthermore, higher uncertainty reduces the value of the effective tax exemption. Also, we find that the (partially progressive) German inheritance tax function by trend promotes standard exemption. The results enable tax planners to make an optimal choice between standard or full exemption and allow for calculating the expected tax burden.

Steuerkomplexität im Vergleich zwischen Deutschland und Österreich – Eine Analyse des Status quo - Hoppe, Thomas; Rechbauer, Martina; Sturm, Susann
Die Komplexität von Steuersystemen gewinnt in der Debatte um den internationalen Steuerwettbewerb zunehmend an Bedeutung. Im vorliegenden Beitrag erfolgt, basierend auf den Daten, die dem Tax Complexity Index (www.taxcomplexity.org) zugrunde liegen, eine umfassende Gegenüberstellung der Komplexität der Steuersysteme von Deutschland und Öster-reich unter Berücksichtigung der Mittelwerte aller Länder. Die Steuergesetze weisen sowohl in Deutschland als auch in Österreich einen verhältnismäßig hohen Grad an Komplexität auf. Bei den steuerlichen Rahmenbedingungen fällt der Grad an Komplexität in beiden Ländern dagegen niedrig aus, wobei Österreich im Durchschnitt weniger komplex ist als Deutschland.

Analyse der Veränderung der zwischenstaatlichen Gewinnaufteilung bei Einführung einer standardisierten Gewinnverteilungsmethode am Beispiel des Einsatzes von 3D-Druckern - Mair, Christina; Scheffler, Wolfram; Senger, Isabell; Sureth-Sloane, Caren

Steuerkomplexität im Vergleich zwischen Deutschland und Österreich - Eine Analyse des Status quo - Hoppe, Thomas; Rechbauer, Martina; Sturm, Susann (Steuer und Wirtschaft)
Die Komplexität von Steuersystemen gewinnt in der Debatte um den internationalen Steuerwettbewerb zunehmend an Bedeutung. Im vorliegenden Beitrag erfolgt, basierend auf den Befragungsdaten, die dem Tax Complexity Index von Hoppe et al. (2019) zugrunde liegen, eine umfassende Gegenüberstellung der Komplexität der Steuersysteme von Deutschland und Österreich unter Berücksichtigung der Mittelwerte aller vom Index abgedeckten Länder. Die Steuergesetze weisen sowohl in Deutschland als auch in Österreich einen verhältnismäßig hohen Grad an Komplexität auf. Bei den steuerlichen Rahmenbedingungen fällt der Grad an Komplexität in beiden Ländern dagegen niedrig aus, wobei Österreich im Durchschnitt weniger komplex ist als Deutschland.

Violations of Dominance in Decision-Making - Kourouxous, Thomas; Bauer, Thomas (Business Research)
A key premise underlying most of the economic literature is that rational decision-makers will choose dominant strategies over dominated alternatives. However, prior literature in various disciplines including business, psychology, and economics document a series of phenomena associated with violations of the dominance principle in decision-making. In this comprehensive review, we discuss conditions under which people violate the dominance principle in decision-making. When presenting violations of dominance in empirical and experimental studies, we differentiate between absolute, statewise, and stochastic (first- and second-order) violations of dominance. Furthermore, we categorize the literature by the leading causes for dominance violations: framing, reference points, certainty effects, bounded rationality, and emotional responses.

Using Impact Evaluation to Examine Domestic and International Cooperative Compliance Programs - Majdanska, Alicja; Wu, Yuchen (Tax Notes International)

Aus Daten müssen Informationen werden - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Investment Timing Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren (Journal of Business Economics)
We analyze the impact of wealth taxes on investment timing decisions under uncertainty and irreversibility by employing a real options model of the Dixit/Pindyck type. Considering that wealth taxes have been (re-)introduced or are under discussion in many countries, investors need decision rules for tax systems with wealth taxation. We integrate different valuation methods for wealth tax purposes, distinguish between broadly and narrowly defined wealth taxes and vary the wealth tax rate to ascertain which wealth tax design is more or less likely to accelerate or delay investment. Our main findings are threefold. First, historical cost valuation reduces the distortive timing effects of wealth taxation compared to fair value accounting. Second, broadening the wealth tax base tends to accelerate investment during high interest rate periods and delay investment during low interest rate periods. Our results predict that wealth taxes with a broad tax base are likely to discourage risky investment in times of near-zero interest rates. These distortive wealth tax base effects, however, can be avoided by granting sufficiently high depreciation deductions for wealth tax purposes. Third, the investment timing effects of wealth tax rate variations are very sensitive to the riskiness of the underlying investment. Moreover, investment timing effects crucially depend upon the depreciation rate for wealth tax purposes. A tax legislator who aims to encourage risk taking should introduce generous depreciation deductions. Our study indicates that if a wealth tax is considered to be politically inevitable, possible harmful investment effects can be mitigated by choosing appropriate valuation methods and parameters.

Ein Lösungsvorschlag zur Vermeidung der überschießenden Wirkung der Grunderwerbsteuerreform bei börsennotierten Kapitalgesellschaften - Arbeitskreis Steuern der Schmalenbach-Gesellschaft für Betriebswirtschaft, .; Sureth-Sloane, Caren (Betriebs-Berater)
Der Beitrag stellt die teilweise überschießende Wirkung des Referentenentwurfs des Bundesministeriums der Finanzen zur Grunderwerbsteuer mit Blick auf börsennotierte Kapitalgesellschaften dar und schlägt eine Erweiterung des Referentenentwurfs vor, wobei börsennotierte Kapitalgesellschaften vom Anwendungsbereich der neuen Vorschrift ausgenommen werden sollen.

What are the Drivers of Tax Complexity for MNCs? Global Evidence - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (Intertax)
All over the world, firms and governments are increasingly concerned about the rise in tax complexity. To manage it and develop effective simplification measures, detailed information on the current drivers of complexity is required. However, research on this topic is scarce. This is surprising as the latest developments-for example, those triggered by the BEPS project-have given rise to the conjecture that complexity drivers may have changed, thus questioning the findings of prior studies. In this article, we shed light on this issue and provide a global picture of the current drivers of tax complexity that multinational corporations face based on a survey of 221 highly experienced tax consultants from 108 countries. Our results show that prior complexity drivers of the tax code are still important, with details and changes of tax regulations being the two most important complexity drivers. We also find evidence for new important complexity drivers emerging from different areas of the tax framework, such as inconsistent decisions among tax officers (tax audits) or retroactively applied tax law amendments (tax enactment). Based on the tax consultants' responses, we develop a concept of tax complexity that is characterized by two pillars, tax code and tax framework complexity and illustrates the various aspects that should be considered when assessing the complexity of a country's tax system.

Tax Avoidance and Accounting Conservatism - Bornemann, Tobias
This study analyzes the relation between accounting conservatism, future tax rate cuts and countries’ level of book-tax conformity. Firms have an incentive to increase conservatism in ﬁnancial reporting when a tax rate cut is imminent to shift taxable income into the lower taxed future. Using a panel of ﬁrms across 18 countries from 1995 to 2010 I ﬁnd that conditional conservatism is positively and signiﬁcantly associated with future tax rate cuts when book-tax conformity is high. This eﬀect is particularly pronounced for ﬁrms that concentrate the majority of their operations in the country in which the tax rate is cut. In contrast, there is no signiﬁcant relation between future tax rate cuts and unconditional conservatism.

Do Transfer Pricing Rules Distort R&D Investment Decisions? - Bornemann, Tobias
This study analyzes the impact of transfer pricing on multinational enterprises’ R&D investment decisions. Speciﬁcally, I examine the eﬀects of two commonly used contract designs to exchange and develop intangible assets across group aﬃliates: licensing and cost sharing agreements. Whilst serving as a tool to allocate taxable income between group aﬃliates, the economic implications of licensing and cost sharing agreements diﬀer. Whereas licensing agreements provide for a sharing rule on the intangible’s proﬁts, cost sharing agreements on the other hand provide a sharing rule on R&D development costs. This diﬀerence matters when ﬁrms simultaneously use internal transfer prices to allocate taxable income and provide local management with suﬃcient investment incentives. Using a multiple-agent, moral hazard investment framework I model a multinational ﬁrm with comparable group afﬁliates in two countries that delegates the R&D investment decision to a local risk and eﬀort averse aﬃliate manager. The results suggest that the optimal contract not only depends on available tax beneﬁts, but also on R&D investment and manager speciﬁc characteristics. A licensing agreement provides management with larger incentives to invest in R&D mitigating agency concerns associated with R&D. On the other hand, using a cost sharing agreement the ﬁrm can cater diﬀerent risk preferences among managers potentially increasing investment. The arm’s length principle however may distort an eﬃcient allocation of R&D costs when using a cost sharing agreement.

Taxation and Agency Conflicts between Firm Owners and Managers: A Review - Bauer, Thomas; Kourouxous, Thomas; Krenn, Peter (Business Research)
When analyzing the influence of taxation on agency conflicts between firm owners and managers, one can draw on theoretical principal–agent literature from various research fields. In recent years, this interdisciplinary research has grown significantly covering research with regards to optimal compensation, investment decisions, tax avoidance and transfer pricing while analyzing the effects of corporate income taxes, wage taxes, bonus taxes and shareholder taxes. Our paper provides a comprehensive review of analytical literature that studies the influence of taxation on agency conflicts between firm owners and managers. Above and beyond summarizing research findings, we discuss how taxes are commonly implemented in agency models, derive empirical predictions, and identify research gaps for future tax research.

Restrukturierungen: operative und finanzielle Wertbeiträge. Eine Betrachtung vor dem Hintergrund der Entwicklungen bei thyssenkrupp - Sievers, Sönke; Sureth-Sloane, Caren; Uhde, André (Die Wirtschaftsprüfung)
Restrukturierungen werden sowohl durch die Digitalisierung, aber auch durch klassische Themen – beispielsweise die Notwendigkeit von Umsatz- und Kostensynergien in kompetitiven Märkten – verstärkt vorangetrieben. Dieser Beitrag beleuchtet vor allem die Motive und Folgen aus wissenschaftlicher Perspektive, indem großzahlige empirische Befunde zu den Themen Beschäftigung, Finanzkennzahlen und Kapitalerhöhungen sowie steuerliche Motive prägnant zusammengefasst und im Kontext des geplanten Joint Ventures von thyssenkrupp und Tata Steel diskutiert werden.